Ospedali e politiche assistenziali a Vicenza nel Quattrocento - Bianchi, Francesco (Reti Medievali E-Book, 2014)
The fifteenth century is the century of hospital reforms, started in numerous Italian cities in order to overcome the inadequacies of traditional charitable practices of the Middle Ages and to face the social and health emergencies of that period with the help of different tools. Vicenza also participated in the reform process, restructuring the organisation of its care network, especially thanks to the intervention of the urban patriciate, which ruled the government of the major hospitals according to "managerial" criteria. In the fifteenth century the search for the bonum commune (common good) thus found expression in a new and rational way of understanding, financing and dispensing charity, conversing with public and private actors of the urban scene: a new but not so revolutionary way, in which ancient and recent feelings converged, such as Christian pietas, civic religiosity and protection of the social class' status quo.